Distracted Driving Classification Based On Driving Skills In Females - Rajoo, Tanish (Universiti Sains Malaysia, 2021)
Driving a car in a real-life is a safety-critical example of multitasking. Distraction is a significant risk to road safety, not only for drivers but also for vulnerable road users. Distracting behaviours while driving are popular all around the world, despite the fact that they have been shown to have a negative influence on driving safety. This study examine distractive driving skills on female drivers. This is done through conducting two different datasets which one from US dataset and another one is Malaysia dataset. Driving experience with more than and equal to one and half a year drivers were considered in this study. Total of 33 and 57 female drivers were chosen respectively in both datasets. Additionally, a class attribute which is DriverDistractionLevel class is introduced with 3 distinct (Mild Distraction, Moderate Distraction and Severe Distraction). Furthermore, driving performance indicator also been listed which were Speed, Brake, Steering, LaneOffset, Lane.Positon and Time. The analysis among the study attributes showed that female drivers highly engaged in the distractive driving based on their driving skills, which is identified by the driving performance indicator.